Quality of Government and the Returns of Investment Examining the Impact of Cohesion Expenditure in European Regions - Rodriguez-Pose, Andrés (OECD Regional Development Working Papers, 2013)
This paper sets out to examine the impact of the quality of local and regional governments on the returns of investment, focusing on the returns of EU structural and cohesion funds. Despite the widespread belief that the quality of government affects the returns of public investments, whether this is effectively the case has seldom been proved. Using primary data on quality of government collected by the Quality of Government Institute, combined with World Bank Global Governance Indicators data, we conduct a two-way fixed effect panel regression model for a total of 169 in European regions during the period 1996 to 2007. The results of the analysis underline the importance of the quality of government both as a direct determinant of economic growth, as well as a moderator of the efficiency of structural and cohesion funds expenditure. Our analysis finds that both EU investments targeting regions and quality of government make a difference for regional economic growth, but that above a significant threshold level of expenditure, the quality of government is the key factor determining the returns of public investment. In many of the regions receiving the bulk of structural funds, greater levels of cohesion expenditure would, in the best case scenario, only lead to a marginal improvement in economic growth, unless the quality of government is significantly enhanced